CHUFA NUT (CYPERUS ESCULENTUS L.) – MINOR VEGETABLE CROP - Y. P. Shevchenko (Овощи России, 2015)
Data on the time of origin and habitat of chufa nut is presented in the article. Brief description, biological particularities, nutrition value, and agricultural technology of this crop in condition of central Russia are described. The possibility of growing the chufa nut were shown in the experiment conducted in the VNIISSOK. The average yield of root nodules in condition of greenhouse was 1.8-2.2 kg/m2.